Advokat Sebagai Penegak Keadilan Antara Etika Profesi dan Jerat Korupsi - Putri Areta Arzety Sinaga; Yesi Nabila Putri; Vanesia Vanesia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Advocates are one of the main pillars in the justice system that have a strategic role as law enforcers, human rights defenders, and guardians of justice. However, amidst high public expectations for the integrity and professionalism of advocates, various serious challenges have emerged, one of which is the practice of corruption that can damage the dignity of this profession. This article aims to examine the position of advocates as enforcers of justice from the perspective of professional ethics and the potential for involvement in corruption. Using a normative legal approach, this article analyzes the legal basis and code of ethics of advocates, as well as real case studies as an empirical illustration.